2001
DOI: 10.1111/1468-0432.00131
|View full text |Cite
|
Sign up to set email alerts
|

Time, Money and the Gender Order: Work Orientations and Working‐Time Preferences in Britain

Abstract: In the context of economic restructuring and the reorganization of working time, the question of working-time preferences is emerging as an important component of both academic and policy debates. Much of the debate about preferences is based upon conjuncture or inadequate indicators, often drawing oppositional models of gender differences in preferences which neglect the similarities between the sexes. This article starts by developing a framework for interpreting preference formation and change, with particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
157
1
20

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(189 citation statements)
references
References 15 publications
(23 reference statements)
8
157
1
20
Order By: Relevance
“…Dutch women's part-time work is on a fairer basis than in the UK, where women's part-time work is particularly poorly valued (Fagan, 2001;Grimshaw and Rubery, 2001;Plantenga, 2002). These policies should enable households to negotiate, adapt and share working hours more equally.…”
Section: Timementioning
confidence: 99%
“…Dutch women's part-time work is on a fairer basis than in the UK, where women's part-time work is particularly poorly valued (Fagan, 2001;Grimshaw and Rubery, 2001;Plantenga, 2002). These policies should enable households to negotiate, adapt and share working hours more equally.…”
Section: Timementioning
confidence: 99%
“…Den kritiseres saerlig fordi den ikke har et kontekstuelt perspektiv og fordi den er statisk: Teorien gir lite rom for individuelle og samfunnsmessige endringer (Crompton & Harris 1998;Fagan 2001). Fagan hevder at en eller flere korte perioder med deltidsarbeid ikke er i konflikt med en sterk dedikasjon til yrket.…”
Section: Hvilken Betydning Har Dedikasjon Til Yrket For Deltidspreferunclassified
“…Numerous studies found that working longer hours or longer days can seriously boost work family conflict (e.g., Shamir, 1983;Greenhaus et al, 1987;Carlson and Perrewe, 1999;Grzywacz and Marks, 2000;Nielson et al, 2001;Fagan, 2001;MacInnes, 2005;Boyar et al, 2008;Russell et al, 2009;Allen and Finkelstein, 2014). Moreover, work family conflict was found to be predicted by greater work demands (e.g., Yang et al, 2000), a greater time commitment to work (e.g., Parasurman and Simmers, 2001), rotating shifts (e.g., Shamir, 1983), higher organisational loyalty (e.g., Tenbrunsel et al, 1995), greater autonomy at work (e.g., Parasurman and Simmers, 2001), inequity rewards at work (e.g., Greenhaus et al, 1987), and working weekends (e.g., Shamir, 1983).…”
Section: Work Related Predictorsmentioning
confidence: 99%